Circumcision for the prevention of urinary tract infection in boys: a systematic review of randomised trials and observational studies. Issue 8 (12th May 2005) - Singh-Grewal, D; Macdessi, J; Craig, J
Abstract : Objective: To undertake a meta-analysis of published data on the effect of circumcision on the risk of urinary tract infection (UTI) in boys. Data sources: Randomised controlled trials and observational studies comparing the frequency of UTI in circumcised and uncircumcised boys were identified from the Cochrane controlled trials register, MEDLINE, EMBASE, reference lists of retrieved articles, and contact with known investigators. Methods: Two of the authors independently assessed study quality using the guidelines provided by the MOOSE statement for quality of observational studies. A random effects model was used to estimate a summary odds ratio (OR) with 95% confidence intervals (CI). Results: Data on 402 908 children were identified from 12 studies (one randomised controlled trial, four cohort studies, and seven case–control studies). Circumcision was associated with a significantly reduced risk of UTI (OR = 0.13; 95% CI, 0.08 to 0.20; p<0.001) with the same odds ratio (0.13) for all three types of study design. Conclusions: Circumcision reduces the risk of UTI. Given a risk in normal boys of about 1%, the number-needed-to-treat to prevent one UTI is 111. In boys with recurrent UTI or high grade vesicoureteric reflux, the risk of UTI recurrence is 10% and 30% and the numbers-needed-to-treat are 11 and 4, respectively. Haemorrhage and infection are the commonest complications of circumcision, occurring at rate of about 2%. Assuming equal utility of benefits and harms, net clinical benefit is likely only in boys at high risk of UTI.